PERSAMI MI Nurussalam: Strategies for increasing students' spiritual intelligence based on natural activities - Nur Hadi Ihsan; Ide Mafaza Sansayto; Humaira Agam Putri; Iradah Dwi Putriani; Nailul Izzah; Syahnaz Nurzaini Bey; Nurul Inayah; Khoffifa Assakhyyu Qorib; Apriliya Dwi Safitri (Journal of Community Service and Empowerment, 2024)
Spiritual intelligence is an important dimension in the holistic development of students. Although intellectual intelligence (IQ) is often the main focus in education, spiritual intelligence also has a significant role in shaping character, morality, and emotional well-being. Islamic Religious subject is one way to develop spiritual intelligence, a phenomenon that occurs at MI Nurussalam. Islamic Religious subject is given at a percentage of 10% of the general subjects’ hours so that religious subject study hours only last for three meetings a week. Universitas Darussalam (UNIDA) Gontor Women’s Campus Postgraduate Community Service Team organized PERSAMI at MI Nurussalam which aimed at increasing student's spiritual intelligence through fun natural activities, namely Saturday and Sunday Camps (Saturday and Sunday Camps – PERSAMI). The method used is PAR (Participatory Action Research), in partnership with MI Nurussalam teachers and students. This community service has succeeded in carrying out a series of activities which generally includes camps, cross country, and happy bonfires with a series of religious subjects in each activity. PERSAMI of MI Nurussalam activities succeeded in increasing students' spiritual enthusiasm and increasing their understanding of religion through fun nature camp activities.